Correlation Between Serum Leptin and Insulin Levels: A Case-Control Study - Dr. Keshavamurthy; Dr. Arjun Shekar; Dr. Basavaraju; Dr. Shiva Kumar; Dr. Vinod Kumar (International Journal of Pharma and Bio Sciences, 2023)
Hypertension (HTN) or high blood pressure (BP) is a chronic disorder in which the pressure exerted on arteries is elevated. Normal BP at rest is below 120/80 mm of Hg. If there is persistent elevation of BP above 140/90 mmHg, it is considered HTN. The prevalence of HTN in obese individuals is twice as high as in the general population. Leptin is an amino acid protein hormone with a molecular weight of around 16kDa. It is a product of the obese gene (ob) from adipocytes. Previous studies revealed the correlation between serum leptin levels and body mass index. The study's novelty is that we assess the correlation between leptin and insulin levels in hypertensive patients. The current study assesses the correlation between hypertensive patients' serum leptin and serum insulin levels. The study's objectives include assessment of age, gender distribution, blood pressure, and comparison of serum leptin and insulin levels among hypertensive and normotensives. This study was conducted among 50 subjects with hypertension(cases) and 50 subjects without hypertension(controls). The study samples were taken from patients who attended the Department of General Medicine outpatient unit at Sri Siddhartha Medical College, Tumkur, Karnataka, India. Results showed that most of the patients were aged 51 to 60 years, and most of the patients were males. There is no significant difference in the gender or mean age between cases and controls. In conclusion, there is a positive correlation between serum insulin and leptin levels among hypertensive and a negative correlation between serum insulin and leptin levels among normotensives. There is a significant difference in the mean serum leptin and insulin levels between hypertensive and normotensives.